PENGARUH STIMULASI PERKEMBANGAN OLEH IBU DENGAN BUKU KESEHATAN IBU DAN ANAK (KIA) TERHADAP PERKEMBANGAN BALITA USIA 12 BULAN DI POSYANDU WILAYAH KERJA PUSKESMAS ROGOTRUNAN KABUPATEN LUMAJANG - Prastyarini, Lufiana Indra; Sary, Yessy Nur Endah; Ermawati, Iit (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Ignorance of parents about toddler development results in an inappropriate response to the growth and development of toddlers, especially at the age of 12 months. Therefore, parents can stimulate child development independently using the Maternal and Child Health Handbook. The study aimed to determine the effect of stimulation of development by mothers with the Maternal and Child Health handbook on the development of toddlers aged 12 months at the posyandu in the working area of the Rogotrunan Health Center, Lumajang Regency. The research method was a Quasi Experimental Design with 20 respondents from mothers of toddlers aged 12 months using the total sampling technique. The instrument used is a progress checklist in the validated Maternal and Child Health handbook. Analysis of the Paired Sample T Test in the Intervention group and the Control group showed differences in the results of the pre-test and post-test. This explained that the stimulation of development carried out by mothers of toddlers independently using guide in the Maternal and Child Health handbook was very effective in accelerating the development of toddlers according to their age. Meanwhile, the developmental stimulation carried out by health workers alone without the toddler's mother stimulating the development of her toddler was less effective. It is hoped that further researchers can examine with a stronger design, respondents of various age groups, and other aspects of development to strengthen the findings of the effect of stimulation of development by the mother on accelerating the developmental abilities of their toddlers.